Strange jets - Veikkola, Emilia (My University, 2024)
This thesis presents an in-depth study of strange jets, with a focus on their prop- erties and the determination of their jet energy scale (JES). Using data from the Compact Muon Solenoid (CMS) experiment at the Large Hadron Collider (LHC), this work addresses the challenges involved in identifying and analyzing strange jets, particularly in relation to other jet flavors. The study is organized into two main parts: First, a Monte Carlo-based study examines strange jets’ particle composition, angular distribution, and jet response. A significant finding is the higher proportion of neutral kaons in strange jets, particularly with high transverse momentum (pT ), which distinguishes them from other jet flavors. The study also reveals that the leading particles in strange jets carry a substantial fraction of the jet’s total energy. Second, a data-based analysis explores the determination of the jet energy scale for strange jets relative to light-flavor jets. Event selection is performed through charm tag, which is based on the theoretical assumption that in W boson decays, the presence of a charm jet indicates a likely accompanying strange jet. Scale factors are derived to verify the differing rates of up/down and charm/strange pairs. By combining multiple observables, such as mass and pT difference, the strange jet JES is quantitatively estimated. The analysis also investigates potential sources of bias, such as helicity effects and pT -dependent charm tagging efficiencies. This work provides a proof-of-principle for determining the strange jet energy scale and outlines possible future directions for strange jet tagging techniques. Furthermore, it demonstrates a clear difference in particle content between strange jets and up/down jets and provides a comprehensive literature review on strange jets.
Keywords: CERN, LHC, CMS, strange quark, strange jet, jet energy scale